Students of learning disability at schools of Bryadaha city in relation of some variables - Dossah, Madina Hussein; Al - Obaidan, Tamadar Saad; Al - Subaihi, Latifa Abdullah (Journal of Educational and Psychological Sciences, 2018)
The study aimed to identify their percentage in the community of the study, and to recognize the errors of students with reading and writing difficulties according to their levels to identify the type of common mistakes, and to identify the causes. To achieve this, a total of 174 female students from 10 schools in Buraidah, Qassim, with low performance, and some performance behaviors in reading, writing and mathematics, were selected in the first survey by nominees. The following tools were used: • The diagnostic tests (language). The tests revealed that 174 students (141) were students whose grades were less than the standard in diagnostic tests and (101) Standard grades for language. 2 - A questionnaire was used to study the case, revealed that out of the (101) case there are 80 students suffering from problems (personal, family and school) the main results are: 1- The percentage of people with learning difficulties was less than 10% (7.40 - 3.32%). With the study community. 2- On reading and writing difficulties, the study found the following results: Ø Academic difficulties (reading and writing) are associated with learning difficulties in all stages of study Ø The respondents showed some variation in the degree of difficulties and not in quality difficulties The higher the number of errors, the greater the difficulty. The learning difficulties in the sample range from severe to severe Higher levels are higher in number and severity of disturbance than upper levels The highest proportion of the sample are pupils in the age of 8-10 years, suffer from writing difficulties more than difficulty reading 4. In case study the study found the school and personality contributed to the emergence and stabilization of difficulty The study made several recommendations and proposals : learning difficulties - case study - reading and writing difficulties